Bentuk, Makna, dan Nilai-Nilai Umpasa dalam Mangadati Pernikahan Batak Toba di Cipinang Besar Kecamatan Jatinegara Kota Jakarta Timur - Anggira Ayu Simaremare; Suntoko Suntoko; Dian Hartati (Universitas Muhammadiyah Surabaya, 2026)
The richness of oral literature found throughout Indonesia consists of various forms, one of which is folk poetry. Folk poetry is an oral form of poetry that develops within traditional societies. One type of folk poetry among the Batak Toba people is called umpasa. One of the uses of umpasa is in the mangadati tradition. The mangadati tradition in Batak Toba weddings presents umpasa, which contains deep meanings and values. This study aims to describe the forms, meanings, and values of umpasa in Batak Toba weddings in Cipinang Besar, East Jakarta. The research method used is qualitative with an ethnographic approach. Data were collected through participatory observation, interviews, and documentation. Data analysis began with data collection, data reduction, data presentation, and drawing conclusions. Eleven umpasa used in Batak Toba weddings were found. The forms found in the umpasa are divided into text, co-text, and context, which are rich in meaning and contain values such as personal values, family values, material values, spiritual values, sociocultural values, and moral values.